PENGARUH SHOPPING LIFESTYLE DAN HEDONIC SHOPPING MOTIVATION TERHADAP IMPULSE BUYING PADA PRODUK KHAS BIMA DI GALERI MUTMAINAH - ramadanti, odesa; Ernawati, Sri (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
Mutmainah Bima Gallery is a souvenir center that sells various products made in Bima, especially woven fabric products. This research aims to determine the significant influence of shopping lifestyle and hedonic shopping motivation on impulse buying of Bima specialty products in the Mutmainah gallery. This type of research is associative using quantitative data. The population and sample in this study were 50 respondents using a purposive sampling technique. Data collection techniques include observation, literature study, and questionnaires. Data analysis techniques use validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, determination tests, t tests and f tests with the help of SPSS version 26 for Windows. The research results show that there is a significant influence of shopping lifestyle and hedonic shopping motivation on impulse buying of Bima specialty products in the Mutmainah gallery.